Exercise leads to sex-specific recovery of behavior and pathological AD markers following adolescent ethanol exposure in the TgF344-AD model - Reitz, Nicole L.; Nunes, Polliana T.; Savage, Lisa M. (Frontiers in Behavioral Neuroscience, 2024)
Human epidemiological studies suggest that heavy alcohol consumption may lead to earlier onset of Alzheimer's Disease (AD), especially in individuals with a genetic predisposition for AD. Alcohol-related brain damage (ARBD) during a critical developmental timepoint, such as adolescence, interacts with AD-related pathologies to accelerate disease progression later in life.The current study investigates if voluntary exercise in mid-adulthood can recover memory deficits caused by the interactions between adolescence ethanol exposure and AD-transgenes. Male and female TgF344-AD and wildtype F344 rats were exposed to an intragastric gavage of water (control) or 5g/kg of 20% ethanol (adolescent intermittent ethanol; AIE) for a 2 day on/off schedule throughout adolescence (PD27-57). At 6 months old, rats either remained in their home cage (stationary) or were placed in a voluntary wheel running apparatus for 4 weeks. Voluntary wheel running recovers spatial working memory deficits selectively in female TgF344-AD rats exposed to AIE and improves pattern separation impairment seen in control TgF344-AD female rats. There were sex-dependent effects on brain pathology: Exercise improves the integration of recently born neurons in AIE-exposed TgF344-AD female rats. Exercise led to a decrease in amyloid burden in the hippocampus and entorhinal cortex, but only in male AIE-exposed TgF344-AD rats. Although the number of basal forebrain cholinergic neurons was not affected by AD-transgenes in either sex, AIE did reduce the number of basal forebrain cholinergic neurons in female rats. Our data provide support that even after symptom onset, AIE and AD-related cognitive decline and associated neuropathologies can be rescued with exercise in unique sex-specific ways.